Geodetic Data for Juneau Icefield Glaciers: Orthophotos, Digital Elevation Models, and Glacier Boundaries ... - Christopher J. Mcneil; Emily H Baker (U.S. Geological Survey, 2019)
his data release provides geodetic measurements collected since the mid-1940s to characterize the surface elevation, area, and motion of glaciers studied by the U.S, Geological Survey. The primary glaciers of focus are the Benchmark Glaciers of North America which include Gulkana, Wolverine, and Lemon Creek Glaciers in Alaska, Sperry Glacier in Montana, and South Cascade Glacier in Washington state (USA). The data include: historic and contemporary glacier boundary outlines, point data from GNSS surveys, Digital Elevation Models (DEM), and orthorectified aerial photos and satellite imagery (Orthos). This data release is updated periodically. Additional data for Lemon Creek Glacier, part of the Juneau Icefield, is available in a separate data release of USGS Benchmark Glacier geodetic data at https://doi.org/10.5066/P9R8BP3K. The data is documented but is not included here in order to avoid duplication. ...